2017
DOI: 10.4149/gpb_2017007
|View full text |Cite
|
Sign up to set email alerts
|

In vitro non-thermal oxidative stress response after 1800 MHz radiofrequency radiation

Abstract: In this study possible connection between radiofrequency exposure (RF) and development of oxidative stress was investigated by measuring impairment in cellular oxidation-reduction balance immediately after RF exposure. Fibroblast cells V79 were exposed for 10, 30 and 60 minutes to 1800 MHz RF radiation. Electric field strength was 30 V/m and specific absorption rate (SAR) was calculated to be 1.6 W/kg. Electromagnetic field was generated within Gigahertz Transversal Electromagnetic Mode cell (GTEM) equipped by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…Collectively, this indicates that the observed effect on DNA methylation and gene expression is not associated with bulk heating of the sample. This data is in line with previous studies that showed biological effects in the absence of significant heat [Velizarov et al, 1999; Yu and Yao 2010; IARC, 2013; Loos et al, 2013; Marjanovic Cermak et al, 2017; Belpomme et al, 2018; Halgamuge et al, 2020; Sharma et al, 2022].…”
Section: Discussionsupporting
confidence: 91%
“…Collectively, this indicates that the observed effect on DNA methylation and gene expression is not associated with bulk heating of the sample. This data is in line with previous studies that showed biological effects in the absence of significant heat [Velizarov et al, 1999; Yu and Yao 2010; IARC, 2013; Loos et al, 2013; Marjanovic Cermak et al, 2017; Belpomme et al, 2018; Halgamuge et al, 2020; Sharma et al, 2022].…”
Section: Discussionsupporting
confidence: 91%
“…This notion is further supported by observations made in hamster (V79) and human (HSF) fibroblasts. Without having a negative effect on viability or leading to cell damage, exposure to 1.8 GHz RF-EMF (SAR: 1.6/3 W/kg, GSM signal or carrier wave) led to an early transient increase in ROS formation which ceased after 24 h of exposure [113,210,211]. In accordance with these conclusions, no evidence for oxidative DNA damage was found in pulmonary fibroblasts, regardless of the exposure duration (1, 4, 24 h) with different doses (SAR: 0.5, 2, 4.9 W/kg) and modulations of 1.95 GHz RF-EMFs (GSM, UMTS, WiFi) [212].…”
Section: Experimental Data On the Effect Of Emf On Skin Epithelial And Cancer Cellsmentioning
confidence: 99%
“…High-frequency EMF from mobile phones and other modern devices has the potential to damage eye tissues; however, its impact on the gene expression levels of some proteins is undefi ned at present. Investigations showed that RF fi elds may cause alterations in the conformation of cellular proteins and the eventual synthesis of stress response proteins (13,28,29). In this study, we investigated whether 1800 MHz RF-EMF alters Hsp27, p38MAPK, EGFR and caspase-3 gene expression levels or not in the rat eye tissue.…”
Section: Discussionmentioning
confidence: 96%